Peran Bank Syariah Indonesia Di Masa Pandemi Dalam Meningkatkan Ekonomi Masyarakat - Fauzi, Mohammad Yasir; Wisesha, Pramudya (Universitas Islam Negeri Raden Intan Lampung, 2022)
The Covid-19 pandemic emerges new challenges for Islamic banking, namely how the bank can maintain people's welfare. The birth of Indonesian Sharia Banks is expected to be able to improve the people's economy during this pandemic. The purpose of this study is to examine the role of Indonesian Islamic Banks after the merger of Islamic Banks of state-owned enterprises. The study uses a qualitative method to understand social phenomena which focus on the analysis of written material based on the context. Data sources are obtained from published documents, textbooks, journals, manuscripts, articles, and trusted websites. It is hoped that the initiation will impact to increase in capital support for various financial sectors and the halal industry in the country. Keywords: Bank Syari'ah Indonesia, the economy of society, the era of the covid-19 pandemic